2013
DOI: 10.1186/1472-6963-13-496
|View full text |Cite
|
Sign up to set email alerts
|

Case managers for older persons with multi-morbidity and their everyday work – a focused ethnography

Abstract: BackgroundModern-day health systems are complex, making it difficult to assure continuity of care for older persons with multi-morbidity. One way of intervening in a health system that is leading to fragmented care is by utilising Case Management (CM). CM aims to improve co-ordination of healthcare and social services. To better understand and advance the development of CM, there is a need for additional research that provides rich descriptions of CM in practice. This knowledge is important as there could be u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 34 publications
2
46
1
Order By: Relevance
“…This might be indicative of the fact that the value of fieldwork is not acknowledged in existing health studies (Bright et al, 2012;Braaf, Manias, & Riley, 2014;Carroll, Iedema, & Kerridge, 2008;Gustafsson, Kristensson, Holst, Willman, & Bohman, 2013). From the studies in Table 2, it becomes apparent that health researchers use the most convenient form of ethnography to explore a particular phenomenon.…”
Section: Blurring Of the Fieldmentioning
confidence: 99%
See 2 more Smart Citations
“…This might be indicative of the fact that the value of fieldwork is not acknowledged in existing health studies (Bright et al, 2012;Braaf, Manias, & Riley, 2014;Carroll, Iedema, & Kerridge, 2008;Gustafsson, Kristensson, Holst, Willman, & Bohman, 2013). From the studies in Table 2, it becomes apparent that health researchers use the most convenient form of ethnography to explore a particular phenomenon.…”
Section: Blurring Of the Fieldmentioning
confidence: 99%
“…Researchers should be explicit about their ontological and epistemological stance to better understand the perspective from which they explore and find answers for their research question. Many authors claim that their study is a ''focused ethnography,'' even though methodological background information commonly focuses on ''qualitative methods'' or ''ethnography,'' in a general manner (Gustafsson et al, 2013;Magilvy, McMahon, Bachman, Roark, & Evenson, 1987;Pino et al, 2013). In conclusion, we recommend that health researchers conducting ethnography be more explicit in detailing their ''tradition and paradigm of inquiry '' (O'Byrne, 2007'' (O'Byrne, , p. 1389.…”
Section: Missing Depth Of Ontological/epistemological Underpinningsmentioning
confidence: 99%
See 1 more Smart Citation
“…Social contacts, physical activity and optimism may improve mental health, while social isolation, ageing and chronic pain may cause it to deteriorate [6]. Gustafsson et al [7] found one theme; Challenging current professional identity based on three sub-themes; 1) Adjusting to familiar work in an unfamiliar role; 2) Striving to improve the health system through a new role; 3) Trust is vital for advocacy [7]. A cross-sectional study by Noël et al [8] compared the self-management learning needs and willingness to encounter non-physician care providers of patients with multimorbidity and those with a single chronic illness.…”
Section: Introductionmentioning
confidence: 99%
“…The participants experienced uncertainty that increased with their experience of side effects, leading to concern that the medication might be harmful. Four other qualitative studies investigated perceptions and experiences of older patients with multimorbidity, mainly from the perspective of physicians [4]- [7]. Bayliss et al [4] revealed that the patients wanted easy access to healthcare, individualized care plans, support from one care coordinator and continuity of relationships with healthcare professionals who had a caring attitude, listened to them and appreciated that their needs were unique and fluctuating.…”
Section: Introductionmentioning
confidence: 99%